(untitled) (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
The Romanian Academy has supported and fostered culture by awarding prizes for original works written in Romanian—covering literature and national history, as well as fields previously lacking specialized literature. These prizes were funded through donations, most often via bequests, with the resulting funds bearing the donors' names. Notable figures among these donors included Prince Alexandru Ioan Cuza, Constantin Năsturel Herescu, Princess Alina Ştirbei, Dumitru Hagi Vasile, Vasile Adamachi, and Alexandru Odobescu. The awards recognized creativity, scientific merit, and elements distinctive to Romanian culture.